Phytochemical Characterization and Assessment of Crude Extracts From Lantana camara L. for Antioxidant and Antimicrobial Activity - Mansoori, Aadil; Singh, Nitesh; Dubey, Sharad Kumar; Thakur, Tarun K.; Alkan, Noam; Das, Subha Narayan; Kumar, Anirudh (Frontiers in Agronomy, 2020)
Phytochemicals with antimicrobial and antioxidant properties have tremendous potential in suppressing both plant and human diseases. Screening and identification of such compounds from diverse plant species is the first step toward realizing their medicinal and agricultural application. In agriculture, application of antimicrobial phytochemicals as part of an Integrated Disease Management strategy would reduce the detrimental residual effect of synthetic chemicals. In the present study, an invasive plant species, i.e., Lantana camara L. was screened for potential antimicrobial and antioxidant phytochemicals. Extracts of leaves (LE) and flowers (FE) from L. camara were tested for their polyphenol content (total phenol, total flavonoid, and total alkaloid) and antioxidant potential [total antioxidant activity, iron chelating activity and enzymatic activity (peroxidase and polyphenol oxidase)]. Both extracts exhibited high antioxidant and free radical scavenging activities with relatively stronger antioxidant activity in the case of whole flower extracts. FTIR and GC-MS also carried out for chemical analysis of crude extracts. FTIR spectral study of LE and FE revealed the presence of different functional groups such as N–H, C–H, OH, C = O indicates the existence of various metabolites in the extracts. GC-MS study revealed the presence of 66 bioactive compounds, of which 19 components were predicted to have various functions like anti-inflammatory, antiandrogenic, anti-tumor, antimicrobial, etc. Furthermore, in vitro antifungal and antibacterial studies confirmed the antimicrobial effect of both LE and FE against phytopathogens like Magnaporthe oryzae, Xanthomonas axonopodis pv. glycines (Xag) and Xanthomonas oryzae pv. oryzae (Xoo). Molecular study further revealed that phytochemicals (Loliolide, Eicosapentaenoic acid, Salicylic Acid Methyl Ester, and Phytol) of Lantana camara could targets MAPK1, PDF, and SUH like enzymes of phytopathogens, which could inhibit their growth. Therefore, L. camara extracts can be an important ingredient in the suppression of plant diseases.